Absorptive Removal of Volatile Organic Compounds From Flue Gas Streams - Ozturk, B.; Yilmaz, D. (Institution of Chemical Engineers, 2006)
The absorption of volatile organic compounds (VOCs) such as benzene, toluene, carbon tetrachloride and methanol into fresh vegetable and lubricant oils, waste vegetable and lubricant oils and water was studied experimentally in a bubble column. Stripping of the VOCs from the saturated oils was also conducted. More than 90% removal efficiency was obtained for benzene and toluene whereas the removal efficiencies for carbon tetrachloride and methanol when oils were used as aborbent where around 80% and 70%, respectively. Water can be used as an absorbent for moderate concentrations (≤2500 ppmv) of methanol. Removal efficiencies of VOCs decreased by the increase of feed gas flow rate and VOC concentration in the feed gas stream. Regeneration and reuse of the absorbent oils are possible, but prolonged times are necessary for the complete removal of VOCs from the saturated oils. Using the waste oils as VOC absorbents has some advantages such as resuse the waste oil, economy in water consumption and reduction in the amount of waste oils enter the wastewater treatment plant. © 2006 Institution of Chemical Engineers.
Keywords: Absorption; Lubricant Oil; Stripping; Vegetable Oil; VOCs; Water